SO2 emission rates and incorporation into the air pollution dispersion forecast during the 2021 eruption of Fagradalsfjall, Iceland - Pfeffer, Melissa A.; Arellano, Santiago; Barsotti, Sara; Petersen, Guðrún Nína; Barnie, Talfan; Ilyinskaya, Evgenia; Hjörvar, Tryggvi; Bali, Enikö; Pedersen, Gro B.M.; Guðmundsson, Gunnar B.; Vogfjorð, Kristín; Ranta, Eemu Johannes; et al. (Elsevier B.V., 2024)
During the low-effusion rate Fagradalsfjall eruption (19 March – 18 September 2021), the emission of sulfur dioxide (SO2) was frequently measured using ground-based UV spectrometers. The total SO2 emitted during the entire eruption was 970 ± 540 kt, which is only about 6% of the SO2 emitted during the similar length Holuhraun eruption (2014–2015). The eruption was divided into five phases based on visual observations, including the number of active vents and the occurrence of lava fountaining. The SO2 emission rate ranged from 44 ± 19 kg/s in Phase 2 to 85 ± 29 kg/s in Phase 5, with an average of 64 ± 34 kg/s for the entire eruption. There was notable variability in SO2 on short timescales, with measurements on 11 August 2021 ranging from 17 to 78 kg/s. SO2 flux measurements were made using scanning DOAS instruments located at different distances from and orientations relative to the eruption site augmented by traverses. Four hundred and forty-four scan and traverse measurements met quality criteria and were used, along with plume height and meteorological data, to calculate SO2 fluxes while accounting for wind-related uncertainties. A tendency for stronger SO2 flux concurrent with higher amplitude seismic tremor and the occurrence of lava fountaining was observed during Phases 4 and 5 which were characterized by intermittent crater activity including observable effusion of lava and gas release interspersed with long repose times. This tendency was used to refine the calculation of the amount of SO2 emitted during variably vigorous activity. The continuous seismic tremor time series was used to quantify how long during these eruption phases strong/weak activity was exhibited to improve the calculated SO2 flux during these Phases. The total SO2 emissions derived from field measurements align closely with results obtained by combining melt inclusion and groundmass glass analyses with lava effusion rate measurements (910 ± 230 kt SO2). Specifically, utilizing the maximum S content found in evolved melt inclusions ...